2021
DOI: 10.1016/j.aninu.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus amyloliquefaciens CECT 5940 improves performance and gut function in broilers fed different levels of protein and/or under necrotic enteritis challenge

Abstract: Two studies were conducted to investigate the effect of Bacillus amyloliquefaciens CECT 5940 (BA) as a probiotic on growth performance, amino acid digestibility and bacteria population in broiler chickens under a subclinical necrotic enteritis (NE) challenge and/or fed diets with different levels of crude protein (CP). Both studies consisted of a 2 × 2 factorial arrangement of treatments with 480 Ross 308 mix-sexed broiler chickens. In study 1, treatments included 1) NE challenge (+/−), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 74 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…We have previously reported that successful subclinical NE challenge was applied in this experiment, as performance traits were significantly affected by the challenge [28]. The NE challenge significantly impaired BWG and FCR in birds, and increased lesion scores in these groups [28].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We have previously reported that successful subclinical NE challenge was applied in this experiment, as performance traits were significantly affected by the challenge [28]. The NE challenge significantly impaired BWG and FCR in birds, and increased lesion scores in these groups [28].…”
Section: Discussionmentioning
confidence: 80%
“…There is a direct correlation between amino acid balance on mucin production [73], thus the improved amino acid uptake could have led to increased expression of MUC2 observed in the current results. We have previously observed the positive effects of BA supplementation on amino acid digestibility [28]. It should be noted that the number of genes evaluated in this study are extremely limited.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… Shini et al (2020) reported that dietary addition of BA-H57 (2.48 × 10 8 CFU/g feed) increased ADG and improved F:G of Ross 308 broilers challenged with Clostridium perfringens fed a wheat-soybean diet. Previous studies on BA-5940 have shown that the addition of BA-5940 (1.0 × 10 6 CFU/g of feed) improved F:G of Cobb 500 broilers challenged with Eimeria and Clostridium perfringens fed a corn-soybean meal diet ( De Oliveira et al, 2019 ), and improved BWG, FI, and F:G of Ross 308 broilers fed wheat-soybean meal diets under necrotic enteritis challenge ( Gharib-Naseri et al, 2021 ). Under commercial production conditions, the present study showed that BA-5940 supplementation improved ADG and F:G of AA broilers fed a corn-wheat-soybean meal diet, which confirmed that ADG and F:G can be improved by BA-5940 supplementation even in unchallenged conditions at different types of diets.…”
Section: Discussionmentioning
confidence: 99%
“…and Clostridium perfringens . Gharib-Naseri et al (2020 ; 2021 ) reported that supplementation with BA-5940 increased serum IgA, IgM, and IgG concentrations, and improved digestibility of cystine, valine, and lysine of broilers under necrotic enteritis challenge. Previous studies on BA-5940 mainly focus on growth performance, carcass trait, digestibility, and immune globulin of broilers under challenging conditions.…”
Section: Introductionmentioning
confidence: 99%